2013
DOI: 10.17221/665/2012-pse
|View full text |Cite
|
Sign up to set email alerts
|

The cell wall-bound phenolics as a biochemical indicator of soil drought resistance in winter triticale

Abstract: The leaf dehydration was accompanied by the highest increase in the content of cell wall-bound phenolics (CPh) during heading (148.3% C; % of control) and in course of drought applied twice during propagation and flowering (130.5% C) of triticale. A statistically significant correlations were obtained only for CPh and parameters of leaf water status and chlorophyll fluorescence. An increase in the content of free phenolics (FPh) under drought conditions was only noticed during the flowering (111.4% C) of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…Aside from contributions to the antioxidant properties of the whole grain diet, phenolic compounds are believed to contribute highly toward the TAC of photosynthetic plant tissues in cereal species to better tolerate abiotic stresses (Hura, Hura, Ostrowska, Grzesiak, & Dziurka, ). In this study, eight durum wheat genotypes were studied in a controlled environment, where durum plants underwent control (12% SWC) and pre‐anthesis water‐deficit stress (6% SWC) treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from contributions to the antioxidant properties of the whole grain diet, phenolic compounds are believed to contribute highly toward the TAC of photosynthetic plant tissues in cereal species to better tolerate abiotic stresses (Hura, Hura, Ostrowska, Grzesiak, & Dziurka, ). In this study, eight durum wheat genotypes were studied in a controlled environment, where durum plants underwent control (12% SWC) and pre‐anthesis water‐deficit stress (6% SWC) treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme activity and effectiveness of non-enzymatic substances of low-molecular weight depend, inter alia, on the degree of leaf cell hydration (Hura et al 2012(Hura et al , 2013. During the experiment, the leaves of all winter oilseed rape seedlings showed a similar level of LWC (Fig.…”
Section: Lwcmentioning
confidence: 98%
“…It was shown that increased content of cell wall phenolics was one of the mechanisms facilitating an adaptation to abiotic and biotic stress factors (Wakabayashi et al 1997;El Modafar & El Boustani 2001;De Ascensao et al 2003;Hura et al 2012Hura et al , 2013.…”
Section: Sph Content and Pal Activitymentioning
confidence: 99%
“…5). Increased content of cell wall-bound phenolics is one of the defense mechanisms utilized by plants undergoing biotic (El Modafar and El Boustani 2001;De Ascensao and Dubery 2003;Mandal et al 2009b) and abiotic stresses (Wakabayashi et al 1997;Hura et al 2012Hura et al , 2013. Phenolic compounds present in the cell wall form crossbridges between the cell wall carbohydrates, binding them with ester and/or ether bonds.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to expect that accumulation of phenolic compounds in the apoplast enhances a hydrophobic nature of the cell wall, because it increases the number of hydrophobic benzene rings in its structure, thus making it less permeable to water. The hydrophobic environment of the apoplast might significantly inhibit the water transport from the symplast to the apoplast and limit the capillary transport of water within the apoplast (Hura et al 2012(Hura et al , 2013. Therefore, it should be taken into account that the hydrophobic environment of the apoplast can induce effective water management, which involves the retention of water in the symplast being the metabolically active cell structure at the cost of dead apoplast structure.…”
Section: Discussionmentioning
confidence: 99%